Professional realization of specialists in medical sanitary physics and sanitary engineering. (February 2019) - Israel, M.; Ivanova, M.; Shalamanova, Ts.; Ivanova, P.
Abstract : In Bulgarian legislation there are basically two medical specialties for physicists and engineers: – medical radiological physics – medical sanitary physics In addition, for engineers, architects, environmentalists, the main medical specialty is: – Sanitary engineering. Here, we focused only on the specialties medical sanitary physics and sanitary engineering that are important for the prophylactic medicine. These training courses last for 3 years, and trainees receive the highest degree of competence in the field of measurement and exposure assessment of physical factors, risk evaluation and management, possible health effects of ionizing and non-ionizing radiation, methods for prevention. Simultaneously, they are trained in the field of occupational and environmental health concerning human exposure to physical factors. Such, they are the best specialists for medical units dealing with imaging and medical treating using non-ionizing radiations (NMR, ultrasound, UV and IR radiation), for the health control bodies of the working and living environment, for ecological expertizes, for occupational health services. Unfortunately, most of them are re-qualified as medical radiological physicists and other professions or they are leaving the country because of better incomes and respect. The BSMPE made big efforts to endorse these specialists in appropriate medical units but without any success: most of the medical units hire incompetent persons without the necessary qualification. Our opinion is that BSMPE should put the question for the professional realization of such specialists in the right places, and to propose changes in the legislation providing in this direction. The first step should be changes in the definition of medical physicist according to the broader definition of IOMP. Next, the legislation should include requirements for qualification of medical sanitary physicists and engineers for working in hospitals, medical/cosmetics/SPA centres, physiotherapy, NMR, occupational health services, control bodies of health, environment, labour ministries, accredited laboratories, occupational safety bodies, administration (ecological evaluation). This requirement is set, also in EU Directives 2013/35/EC and 2010/25/EC for protection of workers exposed to electromagnetic fields and optical radiation.